A monastery on the move : art and politics in later Buddhist Mongolia - Uranchimeg Tsultemin (University of Hawaiʻi Press, 2021)
In 1639, while the Géluk School of the Fifth Dalai Lama and Qing emperors vied for supreme authority in Inner Asia, Zanabazar (1635-1723), a young descendent of Chinggis Khaan, was proclaimed the new Jebtsundampa ruler of the Khalkha Mongols. Over the next three centuries, the ger (yurt) erected to commemorate this event would become the mobile monastery Ikh Khüree, the political seat of the Jebtsundampas and a major center of Mongolian Buddhism. When the monastery and its surrounding structures were destroyed in the 1930s, they were rebuilt and renamed Ulaanbaatar, the modern-day capital of Mongolia. Based on little-known works of Mongolian Buddhist art and architecture, A Monastery on the Move presents the intricate and colorful history of Ikh Khüree and of Zanabazar, himself an eminent artist. Author Uranchimeg Tsultemin makes the case for a multifaceted understanding of Mongol agency during the Géluk's political ascendancy and the Qing appropriation of the Mongol concept of dual rulership (shashin tör) as the nominal "Buddhist Government." In rich conversation with heretofore unpublished textual, archaeological, and archival sources (including ritualized oral histories), Uranchimeg argues that the Qing emperors' "Buddhist Government" was distinctly different from the Mongol vision of sovereignty, which held Zanabazar and his succeeding Jebtsundampa reincarnates to be Mongolia's rightful rulers. This vision culminated in their independence from the Qing and the establishment of the Jebtsundampa's theocractic government in 1911. A ground-breaking work, A Monastery on the Move provides a fascinating, in-depth analysis and interpretation of Mongolian Buddhist art and its role in shaping borders and shifting powers in Inner Asia